A study on drug utilization, evaluation and monitoring of adverse drug reactions in the cardiology department of a tertiary care hospital - Tazneem, Bachi; Mateen, Mohammed; Sameer; Masood, Shaafia; Ayman, Zahra; Yazdani, Nabiha (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Cardiovascular diseases require complex pharmacotherapy, increasing the risk of Adverse Drug Reactions (ADRs). Monitoring drug utilization and ADRs is essential to enhance patient safety. Methods: A prospective observational study was conducted over 3 months (April 2025-June 2025) in the Cardiology Department of a tertiary care hospital. Fifty inpatients aged ≥18 years were monitored for ADRs. Causality was assessed using the Naranjo Scale and WHO-UMC criteria; severity was evaluated using the Hartwig Scale. Results: A total of 50 ADRs were reported, with hematological (36%), gastrointestinal (24%), and cardiovascular (16%) systems most affected. Anticoagulants, antiplatelets, diuretics, RAAS inhibitors, and SGLT2 inhibitors were commonly implicated. Most ADRs were moderate (50%), with 62% categorized as probable. No fatalities occurred; 66% of patients recovered fully. Conclusions: ADRs are common among cardiology inpatients, with polypharmacy and comorbidities as key risk factors. Regular pharmacovigilance, patient monitoring, and individualized therapy are essential to minimize ADR-related complications.